METTL3 attenuates proliferative vitreoretinopathy and epithelial‐mesenchymal transition of retinal pigment epithelial cells via wnt/β‐catenin pathway. Issue 9 (23rd March 2021) - Ma, Xinqi; Long, Chongde; Wang, Fangyu; Lou, Bingsheng; Yuan, Miner; Duan, Fang; Yang, Yao; Li, Jiaqing; Qian, Xiaobing; Zeng, Jieting; Lin, Shuibin; Shen, Huangxuan; et al.
Abstract: Proliferative vitreoretinopathy (PVR) is a refractory vitreoretinal fibrosis disease, and epithelial‐mesenchymal transition (EMT) of retinal pigment epithelial (RPE) cells is the key pathological mechanism of PVR. However, few studies focused on the role of METTL3, the dominating methyltransferase for m6A RNA modification in PVR pathogenesis. Immunofluorescence staining and qRT‐PCR were used to determine the expression of METTL3 in human tissues. Lentiviral transfection was used to stably overexpress and knockdown METTL3 in ARPE‐19 cells. MTT assay was employed to study the effects of METTL3 on cell proliferation. The impact of METTL3 on the EMT of ARPE‐19 cells was assessed by migratory assay, morphological observation and expression of EMT markers. Intravitreal injection of cells overexpressing METTL3 was used to assess the impact of METTL3 on the establishment of the PVR model. We found that METTL3 expression was less in human PVR membranes than in the normal RPE layers. In ARPE‐19 cells, total m6A abundance and the METTL3 expression were down‐regulated after EMT. Additionally, METTL3 overexpression inhibited cell proliferation through inducing cell cycle arrest at G0/G1 phase. Furthermore, METTL3 overexpression weakened the capacity of TGFβ1 to trigger EMT by regulating wnt/β ‐catenin pathway. Oppositely, knockdown of METTL3 facilitated proliferation and EMT of ARPE‐19 cells. In vivo, intravitreal injection of METTL3‐overexpressing cells delayed the development of PVR compared with injection of control cells. In summary, this study suggested that METTL3 is involved in the PVR process, and METTL3 overexpression inhibits the EMT of ARPE‐19 cells in vitro and suppresses the PVR process in vivo.